Relationship between static and dynamic foot postures in professional baseball players - Donatelli, R.; Wooden, M.; Ekedahl, S. R.; Wilkes, J. S.; Cooper, J.; Bush, A. J. (Journal of Orthopaedic & Sports Physical Therapy, 1999)
Abstract: Study Design: Observational study of static and dynamic foot postures in professional baseball players. Background: Throughout the course of a professional baseball season, running, cutting, and sprinting activities can produce a breakdown in players` foot function, causing overuse injuries. Objectives: To investigate the relationship between static and dynamic foot postures; to determine the occurrence of abnormal foot postures in professional baseball players and the incidence of overuse injuries in the lower extremity; and to compare the foot postures of pitchers to those of positional players. Methods and Measures: The foot postures of 74 professional baseball players were evaluated at rest and during gait. Measures of static foot posture were obtained with a goniometer and included the subtalar neutral position, forefoot/rearfoot position, ankle joint dorsiflexion, tibial angle in standing, and calcaneal angle in standing. The FootTrak motion analysis system provided measures of dynamic foot posture (rearfoot supination and pronation) during the stance phase of gait. A questionnaire was completed by players who reported previous lower extremity injuries. The chi-square statistic was used to determine the associations between forefoot position (varus or valgus) and the amount of foot pronation during gait. Results: The forefoot varus and calcaneal valgus in standing was significantly associated with the maximum pronation during the stance phase of gait. Of the 65 players who demonstrated excessive pronation (> 8 degrees), 28 (43%) also reported a previous lower extremity injury. No statistically significant difference occurred, however, between injured and uninjured players with respect to the mean values of static or dynamic foot posture. In addition, foot postures were not associated with a player`s position. Conclusions: Selected measures of static rearfoot and forefoot postures may have value in predicting dynamic rearfoot movement during the stance phase of gait. Excessive pronation in the baseball players we studied was not found to be a significant contributing factor in the development of overuse injuries.